PENINGKATAN HASIL BELAJAR JARING-JARING BANGUN RUANG DENGAN PENDEKATAN PEMBELAJARAN MATEMATIKA REALISTIK - Nazmi, Fitria; Ariani, Yetti; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
THE INCREASED OF STUDENT’S LEARNING OUTCOMES OF GEOMETRY NETS WITH REALISTIC MATHEMATIC EDUCATION METHOD AbstractThe purpose of the research is to describe the student’s learning outcomes of geometry nets with realistic mathematic education method in elementary school. The kind of the research is classroom action research that use qualitative and quantitative approaches including planning, implementation, observation and reflection. The subject of this research are the teacher and 20 students of the fifth grade. The result of observation in first cycle is 82.14%, second cycle is 92.85%, teacher aspect in first cycle is 81.66%, second cycle is 95%, student aspect in first cycle is 78.33%, second cycle is 95%. Student result in first cycle is 74.00, second cycle is 87.70. In conclusion, realistic mathematic education method can increase the student’s learning outcomes of geometry nets . Keyword: Learnig outcomes, realistic mathematic education